Formation temperature of sediment core GeoB22605-1 - Freudenthal, Tim (PANGAEA, 2020)
Temperature probing at the base of the bore hole at site GeoB22605-1 was performed with the sea floor drill rig MARUM-MeBo200 in a borehole drilled with a 103 mm diameter bit. A miniature temperature data logger (MTL) built by ANTARES Datasystems GmbH (type 1854) with a 100 mm long tip was inserted into a modified pilot tube of a core barrel. For a temperature probing the drilling operation was stopped, the temperature probe was inserted into the drill string and pushed into the formation at the base of the bore hole. After a waiting time of about 10 minutes the probe was recovered out of the drill string and drilling was continued. The MTL was pre-programmed prior to loading into MeBo for deployment and recorded data every 6 seconds for a total of 96 hours. Data acquisition is autonomous inside the MTL for the duration of deployment. After recovery, data are downloaded including time stamp and temperature reading. The resolution of the temperature reading is 0.75 to 1.2 mK, the accuracy is about 0.1 K.
Keywords: borehole logging; formation temperature